2012
DOI: 10.1111/j.1556-4029.2012.02084.x
|View full text |Cite
|
Sign up to set email alerts
|

AutoMate Express™ Forensic DNA Extraction System for the Extraction of Genomic DNA from Biological Samples*

Abstract: The AutoMate Express™ Forensic DNA Extraction System was developed for automatic isolation of DNA from a variety of forensic biological samples. The performance of the system was investigated using a wide range of biological samples. Depending on the sample type, either PrepFiler™ lysis buffer or PrepFiler BTA™ lysis buffer was used to lyse the samples. After lysis and removal of the substrate using LySep™ column, the lysate in the sample tubes were loaded onto AutoMate Express™ instrument and DNA was extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 11 publications
1
17
0
2
Order By: Relevance
“…). In general, the DNA yields in this study are comparable or higher than reported for similar skeletal remains in previous studies (). Variation in DNA quantity between the technical replicates was observed (Table ).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…). In general, the DNA yields in this study are comparable or higher than reported for similar skeletal remains in previous studies (). Variation in DNA quantity between the technical replicates was observed (Table ).…”
Section: Resultssupporting
confidence: 86%
“…DNA extraction procedures can be labor-intensive, time-consuming, include toxic chemicals, and be relatively inefficient (4,5). Over the past two decades, several DNA purification methods have developed as faster, simpler, and more effective kit-based technologies with the potential for automation (6)(7)(8)(9)(10)(11)(12)(13). However, despite some advancement in commercial DNA extraction kits, DNA extraction is still relatively time-consuming for skeletal remains due to lengthy sample preparation including cleaning, processing, and the requirement for crushing bone into a fine powder prior to digestion (4,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 32 process intermediate samples of the four drug substances mentioned above were tested by the direct resDNA qPCR method and the residual DNA results were compared with the results obtained from a method using an automated DNA extractor called AutoMate Express (AExp) [9] followed by qPCR (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Los resultados indican que la molécula conservó sus propiedades incluso después de 24 horas en la solución tampón de digestión, es decir que la composición de dicha solución, la temperatura de 56 °C y el tiempo, posibilitaron una digestión eficiente sin sacrificar la integridad del ADN y, además, se obtuvieron cantidades suficientes para lograr un perfil genético sin ganancia (drop-in) ni pérdida (drop-out) de alelos (Liu, et al, 2012;Kitayama, et al, 2010).…”
Section: Resultados Y Discusiónunclassified